Perspektif Kinerja Perusahaan Berdasarkan Intellectual Capital - Totok Haryanto (JSSH (Jurnal Sains Sosial dan Humaniora), 2020)
The purpose of this study was to examine and analize: (1) The influence of Human Capital Efficiency (HCE) to firm’s performance. (2) The influence of Structural Capital Efficiency (SCE) to firm’s performance. (3) The influence of Capital Employed Efficiency (CEE) to firm’s performance. This study is the quantitative research with the population some listed companies at Indonesian Stock Exchange (IDX) for the year 2009 until 2011. Data collection based on the financial statement of the listed company at IDX, and using the purposive sampling methods. The analize used regression and t-test. The findings shown that, HCE (human capital efficiency) was not influence to ROA (return on assets), SCE (structural capital efficiency) positively influence to ROA, and CEE (capital employed efficiency) positively influence to ROA. HCE was not influence to ROE (return on equity), SCE positively influence to ROE, and CEE positively influence to ROE. HCE positively influence to RG (revenue growth), SCE positively influence to RG, CEE positively influence to RG.